KARAKTERISTIK PENGUAPAN AIR DAN KUALITAS MINYAK PADA DAUN KAYU PUTIH JENIS Asteromyrtus symphyocarpa - Mohamad Siarudin; Ary Widiyanto (Jurnal Penelitian Hasil Hutan, 2014)
This paper studies the water evaporation characteristics and oil quality of Astermyrtus symphyocarpa cajuput leaves on various growth level. Sample were obtained from Wasur National Park, Merauke that includes nine plants represent three growth stages: tree, poles and sapling. Three branches were taken from each growth stages representing leaf density: dense, medium and less dense. Initial fresh condition of branches were weighed and water evaporation was calculated as weight reduction of branches during five days consecutive drying. Twelve kilogram of leaves were then distilled in the kettle by means of steaming method. Distillation process were repeated five times to replicate the processes studied and during distilation process which took about 4-5 hours, cajuput oils were collected every 30 minutes. The results show that fresh leaves collected from poles branches were the heaviest leaves that weight 163.56 g/branch, followed by fresh leaves collected from tree and sapling that weight 160.22 g/branch and 142.3 g/branch respectively. The highest water evaporation rate was achieved by tree branches (7.89 g/day), followed by poles (6.47 g/day) and sapling (6.28 g/day). Cajuput oil of Astermyrtus symphyocarpa yield is 0.33%, with the specific grafity of 0.912, refractive index of 1.459, alcohol solubility of 1:1, optical rotation of -2.1 and cineole content of 80%. According to properties mentioned, cajuput oil of Astermyrtus symphyocarpa could satisfy The Indonesian Standard for cajuput oil (SNI 06-3954-2006) and classified as the main (U) oil quality.